Comparative performance of theoretical tools in order to quantify the effect of the electric potential on the vibrational wavenumbers and intensities of the SERS of 2-methylpyrazine adsorbed on a nanostructured silver electrode - Valdivia Mantas, Samuel; Aranda Ruiz, Daniel; Soto-Martín, Juan; Otero-Fernández-de-Molina, Juan Carlos; López-Tocón, Isabel (Wiley, 2022)
The effect of the electrode potential in surface-enhanced Raman scattering (SERS) intensities and wavenumbers of 2-methylpyrazine (2MP) was analyzed on the basis of a resonant charge transfer (CT) mechanism by using a simple theoretical model in which the metallic surface and its charge density were simulated by atomic silver clusters of different size (n) and charge (q), [Agn]q. Two linear silver atoms (n = 2) with zero charge (q = 0) and three linear silver atoms (n = 3) with positive and negative charges (q = ±1) linked to the two nonequivalent aromatic nitrogen atoms in 2MP were taken into account. The wavenumber shifts of the most intense bands and the SERS-CT spectra of these two types of metal-adsorbate supermolecule, [Agn-N1]q and [Agn-N4]q, were calculated by using a time-dependent density functional theory (TD-DFT) method and the independent mode displaced harmonic oscillator (IMDHO) approximation. A comparison of the effect of different levels of calculation, ab initio/DFT, on the predictions from the two theoretical models (isolated adsorbate/supermolecule) is also performed. Only DFT theoretical results of the metal-adsorbate supermolecule allow to explain the main role of the pair of bands assigned to totally symmetric ring-stretching 8a,b modes. The 8a vibration is the strongest band at any electrode potential, whereas the 8b mode reaches a maximum enhancement at −0.50 V and then decreases at −0.75 V. This model of a charged metal-adsorbate interface allows for detecting the presence of a CT mechanism in a SERS record.
Keywords: Efecto Raman; Espectroscopía Raman; Transferencia de carga; 2-methylpyrazine; SERS spectroscopy; TD-DFT calculation; Charge transfer mechanism; Nanostructured electrode